Photoluminescent Materials for Solid‐State Lighting: State of the Art and Future Challenges. Issue 4 (2nd January 2015) - Meyer, Jörg; Tappe, Frank
<x xml:space="preserve">Abstract</x> The efficient generation of white light by phosphor‐converted LEDs (pcLEDs) suffers from a trade‐off between high color rendition, low correlated color temperatures, and luminous efficacy. While this is partially an inherent problem, it is also caused by the spectral efficiency of the materials used. The particular challenges for materials research lie, amongst the demanding general requirements, in finding very narrow‐band or line‐emitting materials: excitable with blue light, emitting in the near red. A way to design Mn(IV) activated line emitters is proposed, and methods for high‐throughput combinatorial syntheses are specified.